PENGEMBANGAN TAMAN GIZI SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA KLATAKAN KECAMATAN TANGGUL KABUPATEN JEMBER - Musfiroh, Luluk; Wati, Siska Nur Febilah; Al Jeffry, Mochammad Iqbal; Putri, Nur Aniza Cahyaning; Nurinasamsi, Nazwa; Cahyani, Arini Berlian (Jurnal AbdiMas Nusa Mandiri, 2025)
Stunting is a significant health issue in Indonesia, including in Jember Regency, which still faces a high prevalence rate. Without proper intervention, stunting can hinder development and reduce the quality of life for affected children. Efforts to reduce stunting rates are being made through various programs, one of which is the development of a nutrition garden. This program is based on a Participatory Action Research (PAR) approach and aims to improve community knowledge and nutritional practices by utilizing household yard spaces. The nutrition garden employs a hydroponic farming system to grow various nutritious vegetables, such as chili, spinach, and mustard greens, which are distributed to families with young children, pregnant women, and breastfeeding mothers. Through intensive education and mentoring, the nutrition garden is expected to meet the nutritional needs of the local community, raise awareness about the importance of a balanced diet, and effectively reduce stunting rates in Klatakan Village. This study reveals that the "Nutrition Garden Development Program in Klatakan Village, Tanggul District, Jember Regency" has successfully enhanced community understanding and participation in stunting prevention efforts by utilizing household yards to grow nutritious vegetables through hydroponic methods.